Baltikinin: A New Myotropic Tryptophyllin-3 Peptide Isolated from the Skin Secretion of the Purple-Sided Leaf Frog, Phyllomedusa baltea - Daning Shi; Xinping Xi; Lei Wang; Yitian Gao; Chengbang Ma; Hang Chen; Mei Zhou; Tianbao Chen; Chris Shaw (Toxins, 2016)
Here we report the identification of a novel tryptophyllin-3 peptide with arterial smooth muscle relaxation activity from the skin secretion of the purple-sided leaf frog, Phyllomedusa baltea. This new peptide was named baltikinin and had the following primary structure, pGluDKPFGPPPIYPV, as determined by tandem mass spectrometry (MS/MS) fragmentation sequencing and from cloned skin precursor-encoding cDNA. A synthetic replicate of baltikinin was found to have a similar potency to bradykinin in relaxing arterial smooth muscle (half maximal effective concentration (EC50) is 7.2 nM). These data illustrate how amphibian skin secretions can continue to provide novel potent peptides that act through functional targets in mammalian tissues.